Driver performance due to small unmanned aerial system applications in the vicinity of roadways. (January 2020) - Ryan, Alyssa; Fitzpatrick, Cole; Christofa, Eleni; Knodler, Michael
Highlights: Small unmanned aerial systems (sUASs) are currently flown near roadways. This driving simulator study placed sUAS next to drivers on the roadside. In 11% of analyzed cases, drivers were taking critically long glances of the sUAS. Drivers are equally distracted by sUASs independent of their age and gender. Visual distraction did not vary between three different sUAS altitudes. Abstract: Small unmanned aerial systems (sUAS), or drones, have become increasingly utilized for a myriad of applications in the vicinity of roadways and can offer a low-cost alternative to many labor-intensive data collection techniques, including infrastructure inspection, roadway marking data collection, and more. To collect much of this data with a desired degree of accuracy, sUAS must be flown near moving vehicles, pedestrians, and/or bicyclists. However, sUAS, and their operators, have the potential to be a distraction to drivers. Through a full-immersion driver simulator study and post-experiment questionnaire, this study furthered the current state-of-the-literature and investigated the potential for sUAS to be flown in the vicinity of roadways in the future as well as potential safety implications of those circumstances. Specifically, driver performance due to drone height and the presence of drone operators was evaluated. The results of the driving simulation study revealed that participants were more visually distracted in situations where the operators and drone were both present compared to the drone only scenarios. Furthermore, in 11% of all analyzed situations, drivers were critically visually-distracted as shown by a continuous glance of two seconds or more at the drone or operators. The post-experiment questionnaire revealed that approximately 30% of participants had seen a drone in flight near a roadway prior to this study. Ultimately, this research provides recommendations to policymakers for creating regulations on the use of sUAS in the vicinity of roadways.